Dorsal Onlay Urethroplasty Using Buccal Mucosal Graft and Vaginal Wall Graft for Female Urethral Stricture; Outcome of a Tertiary Care Hospital - Raza Ul Hassan, Shahid Siraj, Ajmal Khan, Amjad Saleem, Iftikhar Ahmad, Raja Naeem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Normally female urethral stricture (FUS) is uncommon and underdiagnosed condition. It is raising a diagnostic challenge for the physicians. It is the one of the rarely known urological entity. Urethral dilatation is the traditionally used treatment for urethral stricture (FUS). The female urethroplasty have shown the promising outcomes. Objective: The objective of the study was to compare the outcome of the dorsal onlay urethoplasty FU obtained by using buccal mucosal graft and vaginal wall graft. The FU is more effective treatment for female urethral stricture (FUS) as compared to the repeated dilatation. Study design: It is a retrospective study with the statistical approach, conducted at Urology Department, Pakistan Institute of Medical Sciences Islamabad from June 2021 to November 2021. Material and Methods: The women who underwent the dorsal onlay urethropasty at the urology department of the hospital were included in the study. The outcomes of BMG and VWG were compared. The re-intervention was marked as failure. The association symptom score, postvoid residual urine (PVR), cystourethrogram, cystoscopy and uretheral calibration were included in the assessment. Operating time, catheter time, etiology, location, length, prior interventions and suprapubic cystostomy were the other parameters that was also reported. For the statistical analysis the Mann-Whitney test, t-test and proportion test was performed. Results: The calculated mean age of the patients included in the group was 48 years. Its range was between the 26 to 76 years. The women visited the urology department of the hospital from June 2021 to June 2022. The average follow-up was for 26 months. The AUA symptoms changes from 22 to 6, Qmax from 4ml/s to 26ml/s and RVR from 185ml to 7ml. The operating time was the only parameter showed the difference, while other remained the same. The 94% was the overall urethral patency rate. Conclusion: For the substitution of dorsal onlay urethroplasty the use of VWG and BMG is highly recommended. It is an efficient and reliable treatment method. There are very low chances of complication and it has an easy protocol. Apparently, no specific change was observed in the FUS treatment by BMG and VWG. Keywords: Female urethral stricture (FUS), buccal mucosal graft, vaginal wall graft, postvoid residual urine (PVR), dorsal onlay urethroplasty.